Menumbuhkan Kesadaran Kewarganegaraan di Kalangan Anak-Anak SD: Implementasi Program Edukids - Muh. Khaerul Ummah BK; Syaiful Hidayat; Hamna; Karmila Risa Rahmawati; Ni’mah Wahyuni; Mustakim; Anggraini Insiano, Dewi (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
Growing civic awareness is important because it incorporates the practice of Pancasila values, which are the foundation of life, nation and state. It needs to be done from an early age, starting from basic education to become the next generation and future leadership relay holders. The main aim of this research is to increase children's citizenship awareness at the elementary school level through teaching activities designed through the Edukids Program with a civic perspective, such as unity, diversity and participation in social life. This research method is descriptive qualitative, which is used to describe and analyze with an argumentative-contextualistic approach regarding the implementation of the "EduKids" program involving fifth-grade students at Pulias Abaling State Elementary School and PGSD students at Madako University Tolitoli third semester class of 2022 as research subjects. The stages of research implementation were observed using direct observation techniques and interviews. Data were analyzed using the interactive approach of the Miles and Huberman model including selecting informative data, presenting data, and drawing conclusions from research results. This program is designed with an interactive, results-oriented approach, including the use of stories, practices and games during the learning process. As a result of this research, information was obtained that the implementation of the "EduKids" program in class V of Pulias Abaling State Elementary School succeeded in increasing elementary school children's understanding of their rights and obligations as citizens, and they began to actively participate in social activities at school and in the community where they live.